What do we know about breastfeeding and COVID-19? - Staff Writer (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2021)
This paper summarises the present recommendations on counseling breastfeeding mothers during the COVID-19 pandemic. The present research shows that breastfeeding by infected, and vaccinated, mothers is safe. So, the overriding advice to mothers in South Sudan, and elsewhere, is to carry on giving the same messages: to start suckling immediately after birth, to exclusively breastfeed for the first six months, and to breastfeed with complementary foods until at least two years of age. COVID-19 hygiene messages should be explained to mothers, their families, and informal midwives/health workers taking into account local beliefs and resources.